Application of Traditional Chinese Medicine in Postoperative Rehabilitation for Anterior Talofibular Ligament Rupture - Xinxin Yang (International Journal of Biology and Life Sciences, 2026)
The anterior talofibular ligament (ATFL) plays a critical role in ankle stability, yet it is the most commonly injured ankle ligament. Thus, its postoperative rehabilitation has become a crucial clinical issue. With the development of Traditional Chinese Medicine (TCM), TCM-based rehabilitation, in its turn, has been receiving more and more attention. This paper is a systematic review of the research studies on the use of TCM interventions in the rehabilitation of postoperative ATFL rupture. Findings indicate that the combination of TCM and conventional Western medicine exerts a significant positive effect on improving ankle motor function, alleviating local pain and swelling, shortening the overall recovery period and delivering effective, cost-effective and high-quality clinical care. Yet, the existing studies have weaknesses such as small sample sizes, lack of high-quality evidence, as well as poor interventions standardization and low international awareness. There is also the lack of integration of Western medicine with TCM because of the lack of interdisciplinary cooperation. This paper helps to confirm the clinical value of TCM in ATFL rupture rehabilitation, promote the international acceptance and application of TCM-based rehabilitation, facilitate the integration of TCM and Western medicine, and lay a more robust theoretical foundation for the development of clinical practice in ankle injury rehabilitation.